The Impact Of Accounting Conservatism And Intellectual Capital On Information Asymmetry In Technology Companies On The Indonesia Stock Exchange - Sudyantara, Smita Catur; Dewi, Susantriana (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
This study aims to empirically examine the impact of accounting conservatism and intellectual capital on information asymmetry in technology sector companies listed on the Indonesia Stock Exchange (IDX). Based on agency theory (Jensen & Meckling, 1976) and signaling theory (Spence, 1973), technology companies inherently have a high level of information asymmetry due to the dominance of intangible assets and high research and development costs that are difficult to assess conventionally. Sampling in this study was planned using a purposive sampling method for technology issuers on the IDX with a multi-year observation period. The accounting conservatism variable was measured using market-based profit and loss recognition prudence indicators (Basu, 1997), while intellectual capital was measured using the Value Added Intellectual Coefficient (VAIC) model developed by Pulic (2000). Information asymmetry was proxied by capital market indicators in the form of stock bid-ask spreads (Leuz, 2003). Data analysis was performed using a panel data multiple linear regression model. The test results are expected to show that both the application of accounting conservatism and the optimization of intellectual capital management have a negative and significant effect on information asymmetry. Compliance with the principle of accounting prudence and transparency in intellectual capital disclosure can be a positive signal that reduces the information gap between internal management and external investors (Barth et al., 2001). This research provides strategic implications for investors in accurately assessing digital business valuations and for capital market authorities in formulating regulations for relevant information disclosure in Indonesia's digital economy era.